2004
DOI: 10.1002/ajp.20054
|View full text |Cite
|
Sign up to set email alerts
|

Use of primates in research: A global overview

Abstract: We assessed the use of nonhuman primates and nonhuman primate biological material in research by reviewing studies published in 2001 in peer-reviewed journals. The number and species of primates used, the origin of the animals, the type of study, the area of research of the investigation, and the location at which the research was performed were tabulated. Additionally, factors related to the animals that may have affected the outcome of the experiments were recorded. A total of 2,937 articles involving 4,411 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
158
0
7

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 206 publications
(165 citation statements)
references
References 23 publications
0
158
0
7
Order By: Relevance
“…This taxonomic group includes vervet monkeys (Chlorocebus aethiops), rhesus macaques (Macaca mulatta), cynomolgus monkeys (Macaca fascicularis), and baboons (Papio hamadryas) (6). Despite the relevance of primate study to human disease research, there has been a shortage of primates available for biomedical research (7). Baboons and humans share great genetic similarity, with ϳ96% homology evident at the DNA level (8).…”
mentioning
confidence: 99%
“…This taxonomic group includes vervet monkeys (Chlorocebus aethiops), rhesus macaques (Macaca mulatta), cynomolgus monkeys (Macaca fascicularis), and baboons (Papio hamadryas) (6). Despite the relevance of primate study to human disease research, there has been a shortage of primates available for biomedical research (7). Baboons and humans share great genetic similarity, with ϳ96% homology evident at the DNA level (8).…”
mentioning
confidence: 99%
“…Both the increasing public criticism and pressure against research involving animals, especially on studies involving non-human primates [12], and the inclusion of the 3R principles in recent regulatory guidance updates, call for attempts to reduce the number of animals used for nonclinical toxicology studies. Recent efforts have been focused on the critical analysis and subsequent optimization of non-human primate study designs because the demand for toxicity testing in nonhuman primates, mostly in Cynomologus monkeys, is increasing due to the heavily growing share of large molecule drugs in the biopharmaceutical industry pipeline.…”
Section: Editorialmentioning
confidence: 99%
“…The continuous increase of its use is due to the fact that the alternative species to the use of Rhesus monkeys, being of management relatively easy and high prolificacy in captivity (Freimer et al 2007). Carlsson et al (2004), carried out a survey of the use of non-human primates in biomedical research, and only in 2001, it was observed that the species was the most used one in published researches of the whole world, mainly in the areas of microbiology and biochemistry, with emphasis on research using the cultivation of cells.…”
Section: Introductionmentioning
confidence: 99%